Studi Interaksi Sosial Mahasiswa Introvert: Kasus Pergaulan Akademik Pada Program Studi PGSD UMK - Risqia Putri, Agustina; Anggi Dwi Putri; Karima Noor Malikatus Sa’adah; Nur Fajrie; Sekar Dwi Ardiyanti (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This study aims to analyze the relationship between introverted personality and the ability to interact with students of the Elementary School Teacher Education Study Program (PGSD) who have communication skills as a provision for elementary school teacher candidates. This study used a qualitative research method with a case study type and used data collection instruments with interview and observation techniques on several students and female students who have introverted personalities. The results of the study found that interaction patterns were influenced by internal factors related to willingness and interest in becoming PGSD students. While external factors on the ability of PGSD students to interact socially in academic association. The introverted personality of PGSD students tends to be antisocial and aloof in academic relationships on campus.